The Prevalence of Metabolic Syndrome and its Components among Ethnic Dayak Community in Sarawak - Koa, Ai Jiun; Cheah, Whye Lian; Yew, Ting Ting; Madzlifah, Ahadon (Faculty of Medicine And Health Sciences, Universiti Putra Malaysia, 2024)
Introduction: Metabolic syndrome (MetS) is a condition that includes a cluster of risk factors, which will lead to increase risk of cardiovascular diseases. Global increase in MetS is likely to affect Malaysia as well, however there is a scarcity of data on MetS among Malaysians. Ethnicity plays a vital role on prevalence and incidence of MetS across different ethnic groups. This is important especially in a multi-ethnic country like Malaysia. However, two most notable studies on MetS across different ethic groups in Malaysia were about a decade ago in 2012 and 2016. The objective of this study is to ascertain the prevalence of MetS among the Dayak communities and the risk factors affiliated with it, and hopefully will serve as a platform for future in-depth researches on MetS across different ethinc groups in Malaysia. Materials and methods: SThis is a cross sectional study that is conducted in various Dayak villages, which are located in Kuching, Semarahan and Serian District in Sarawak. Using a multi-stage sampling, we recruited 353 respondents aged between 18 to 88 years old. Data was collected using questionnaires, blood samples, blood pressure monitor and anthropometric measurements. Descriptive test, chi-square test and logistic regression were conducted to analyse all the available datas. All datas are analyzed using SPSS version 25. Results: A total of 34.6% of the respondents fulfilled the criteria of MetS. Elevated triglyceride (TG) is the strongest predictor of MetS among the five components of MetS in our study population. The prevalence for the components of MetS is as follow: elevated fasting glucose (66.2%), high blood pressure (50.4%), elevated triglycerides (47.3%), central obesity (20.9%) and for low HDL-cholesterol (18.9%). Body mass index and waist-to-hip ratio were identified as the most important risk factors in the MetS prediction models for this population.Higher education level and higher level of physical activity appear to have protective effect against MetS. Traditional cardiovascular risk factors including gender, smoking and alcohol consumption are not related with higher prevalence of MetS in Dayak communities. Conclusion: Approximately one in three ethnic Dayak in Sarawak will have metabolic syndrome in their lifetime. Targetted health education particularly among communities with lower education levels as well as incorporating culturally sensitive and community based interventions can be effective in managing MetS.